If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5+7h=6h+2
We move all terms to the left:
5+7h-(6h+2)=0
We get rid of parentheses
7h-6h-2+5=0
We add all the numbers together, and all the variables
h+3=0
We move all terms containing h to the left, all other terms to the right
h=-3
| n-2/4=2 | | -5+b=4 | | 48=t/9+46 | | K(-3)=4x^{2}-1 | | -14(v-19)=14 | | 37^2=x^2+12^2 | | -4-7c=-9c | | -3–5w=-14 | | 40x+25=50+20x | | 0.25t=2 | | 5.7y=17 | | 6(r-88)=48 | | 2x²-20x+5=0 | | 3x+2=5x–3 | | 55=1+9y | | 2x+8=-2.5x+19 | | 8v=6+7v | | -3+6c=4+2c+-2c | | 3-2x=13+3x/4 | | 8x+11=-x+7x+1 | | 3x^2-5x=-2x-4 | | 14=3x2(-3x+11) | | x-11/4=3/8 | | 20=9u-7 | | (3y+5)=(2y+1) | | 40+6x=x-3(-4x+3) | | 3(x-7)=2x-10 | | 6(n=1)=2(2n+4) | | 6n+8=8n-10 | | 4(5^x-20)=20 | | 10/3=v+4/3 | | w²+6w-122=0 |